ZnO nanoparticles stimulate oxidative stress to induce apoptosis of B16F10 melanoma cells: In vitro and in vivo studies. (20th September 2021) - Fan, Ping; Yang, Congling; Wang, Li; Wang, Qiling; Zhang, Yan; Zhou, Jie; Weng, Jie; Feng, Bo
Abstract: Melanoma is one of the most aggressive skin cancers. However, there remain many limitations in the current clinical treatments of it. Zinc oxide nanoparticles (ZnO NPs) have been considered to be a promising antitumor drug due to their excellent biocompatibility, biodegradability and biofunctionality. In this study, we prepared spherical ZnO NPs with an average diameter of less than 10 nm by a simple chemical method. According to the in vitro cytotoxicity assay, ZnO NPs in a certain concentration range (20–35 μ g ml −1 ) showed significant cytotoxicity to B16F10 melanoma cells, while having little effect on the viability of 3T3L1 fibroblasts. When cultured with B16F10 melanoma cells, ZnO NPs induced the generation of reactive oxygen and mitochondrial superoxide through the release of Zn 2+, leading to oxidative stress in the cells, further reducing the mitochondrial membrane potential and decreasing the number of mitochondrial cristae. Furthermore, damaged mitochondria induced the release of apoptosis factors to promote cell apoptosis. FITC-Annexin V/propidium iodide double staining assay was used to analyze different apoptosis stages of B16F10 cells induced by ZnO NPs. A polymer hydrogel (Gel-F127-ZnO NPs) with Pluronic F127 as the carrier of ZnO NPs was fabricated for evaluating the antitumor effect of ZnO NPs in vivo . The in vivo experiment indicated that the tumor recurrence was significantly inhibited in tumor-bearing mice after treated with Gel-F127-ZnO NPs. Conclusively, ZnO NPs showed a strong antitumor effect both in vitro and in vivo .